The Rising of the Rightist Populist Parties in Europe - Özkan, Hakan Can Ahmet (Journal of History Culture and Art Research, 2018)
In this study, the rise of the rightist populist parties in the European Union (EU), especially because of the recent economic crisis, is comprehensively examined. In the study, the economic crisis and identity problems in the European Union are analyzed. The results of elections in countries such as Austria and France, and their effect on the EU elections, are subjected to analysis. The current crisis of the EU increasingly engages the people in the member and non-member nations. The European citizens hardly define themselves as EU citizens and they consider the old political movements as elitist and distant to citizens. The identity losses in Europe because of wrong policies caused by Germany and France hegemony damages the EU spirit, and as a result, the nationalist movements are getting stronger.